Proposed new interior design of boutique hotel at Lot 9575, Off Jalan Raja Dr Nazrin Shah, 31350 Ipoh, Perak Darul Ridzuan for Al-Jabbar Group Sdn. Bhd. / Abdurrauf Mustafa - Mustafa, Abdurrauf (2012)
This project is proposed new interior design scheme of boutique hotel at No.9575, Off Jalan Dr. Nazrin Shah, 31350 Ipoh, Perak Darul Ridzuan. The client of this project is Al-Jabbar Group Sdn. Bhd. as a well known healthcare products suppliers. With 2 years experience in hospitality services, Al-Jabbar Group Sdn. Bhd. has a will to expand their hospitality services entire region in Malaysia. The aim of this project is to help Al-Jabbar Group Sdn. Bhd. to promote their products and services to community. Objectives this project is to design a Hospitality design which is a boutique hotel as a approach to create a comfortable space to gives the best services, facilities and products of Al-Jabbar Group itself. New proposed site located at Ipoh near to Medan Gopeng bus station gives advantages to the building with total area 27,000 sft in overall. Modishness as a concept with the statement prevailing modernism in style applied in design of this Al-Jabbar Hotel.